THE ROLE OF RELIGIOUS MODERATION AMBASSADOR AT MADRASAH ALIYAH (ISLAMIC SENIOR SCHOOL) IN PEKANBARU - Yundri Akhyar; Wirda Ningsih (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2023)
The Religious Moderation Ambassador is a very important position in schools and madrasahs that focus on religious education. The ambassador's position is to encourage religious understanding, moderation, and tolerance among the students. The research aim is to find out the roles of religious moderation ambassadors at Madrasah Aliyah Islamic Senior School) in Pekanbaru. The research was used qualitative approach. The data collection technique was interview document, text, video analysis. The data analyse by using thematic analysis approach. The sample was taken by using purposive sampling technique. 6 religious moderation ambassadors were chosen as the participants of the research. The research fundings were the roles of religious moderation ambassador are promoting tolerance and pluralism, organizing interfaith activities, being conflict resolution, role model in integrating religious moderation into the school environment